Microwave Irradiation Assisted Synthesis 4-Hydroxy 3-Iodobenzylguanidine(HIBG) - Poursharifi, M.; Shahi, S. (Ciência e Natura, 2015)
Meta-iodo benzyl guanidine(MIBG) is an analogue of Noradernalin transmitter. When radiolabelled with 123 I and 131I , used for scan and diagnosis Adernal’s tumor. Labeled MIBG with 131I used in therapy of Neuroblastoma , Pheochromocytoma , Carcinoidsyndome and Neuroendocrine tumors. In our continuing efforts to develop MIBG analogues with higher therapeutic efficacy, we recently evaluated the structure-activity characteristics of several analogues of MIBG. We are interested in developing HIBG analogues containing hydroxyl at the 4-postion oF HIBG.generous of the some groups to activate the aromatic ring of a drug towards electrophilic radiodiodination may have merit .The resistance of HIBG to in vivo radiodiodination and amenability to kit production make it a strong candidate for clinical evaluation as a pheochromocytoma and neuroblastoma localzing agent. Microwave assisted heating under controlled conditions has been shown to be an invaluable technology for organic chemistry and during discovery applications since it often rise yield and dramatically reduce reaction times, typically form days or hours to minutes or even seconds.Microwave Irradiation Assisted Synthesis of HIBG is started to produce 4-methoxybenzylamine. 4-methoxybenzylamine and hydriodic acid are mixed and heated for this purpose. Then under MBR condition 4-Hydroxybenzyl guanidine in sulphate form is prepared with additional Cyanamide and Sulphuric acid. After that Iodination is preformed under MBR condition and 4-Hydroxy-3-iodobenzyl guanidine sulphate formed , that can labeled with 131I and exchange to labeled 4-Hydroxy-3-iodobenzyl guanidine sulphate.